An Analysis of the Legal Responsibility of Team Physicians for ACL Injuries Among Indonesian Liga 1 Players in Light of Law Number 17 of 2023 on Health - Pradnyana, Putu Yudi; Astariyani, Ni Luh Gede; Budiasa, I Wayan (Westscience Press, 2025)
This study analyzes the legal liability of team doctors in cases of Anterior Cruciate Ligament (ACL) injuries in Indonesian League 1 players, reviewed from Law Number 17 of 2023 concerning Health. The background of this study is based on the high risk of ACL injury in professional football athletes and the complexity of applying medical care standards in the context of sports. The method used is normative legal research with statute, conceptual, and case approaches, utilizing primary materials (Law 17/2023, Criminal Code, PSSI/LIB regulations), secondary (health law journals, sports medicine books), and tertiary (legal dictionaries). The results of the study show that the responsibility of team doctors includes civil, criminal, ethical, and administrative dimensions; Law 17/2023 strengthens the accountability framework through Article 440 concerning criminal sanctions for medical negligence, as well as the rights and obligations of patients-athletes. However, it is evident that there is a gap in the qualification standards of Liga 1 team doctors and the absence of specific protocols for handling ACL injuries, which makes it difficult to prove negligence. The main recommendations include improving medical qualifications, drafting detailed protocols, and socializing obligations based on Law 17/2023 to clarify treatment standards and strengthen athletes' legal protection.